Studi Morfotektonik Daerah Ereunpalay, Kabupaten Tasikmalaya, Jawa Barat - Siska Wulandari; Edy Sutriyono (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Morphotectonics is a major factor in controlling the development of landforms and has an influence on river systems in the Ereunpalay area and its surroundings. This study uses a quantitative method, starting with a broad perspective and then moving on to a more focused and targeted approach. This tectonic geomorphological analysis uses several morphometric parameters, such as: Drainage Density (Dd), Bifurcation Ratio (Rb), Valley Floor Width to Valley Height Ratio (Vf), Mountain Front Sinousity (Smf), Hypsometric Curve and Hypsometric Integral (HI), and the Tectonic Activity Index (IAT). From the results of IAT calculations, it is found that the Ereunpalay area and its surroundings are in class one to three tectonic activities or commonly called moderate to very high class. The flow pattern of the river that dominates the study area is a parallel flow pattern which is controlled by the geological structure. Based on the results of the morphotectonic analysis, it was found that the Ereunpalay area and its surroundings have a morphological shape that is influenced by tectonic activity in the form of faults and folds.